Comparative Study of the Biochemical Properties of the Fruits of Wild (Lycopersicon pimpinellifolium Jusl. (Mill.)) and the Cultivated (L. esculentum Mill.) Tomato Cultivars in Nigeria - Adedeji, O.; Adewale, I. O (2014)
The fruits of three cultivars of the cultivated tomato (Lycopersicon esculentum) and the wild species (L. pimpinellifolium ) were analysed and compared for their biochemical properties. Ripe fruits at the orange-red stage were used for all the analyses. Both the cultivated and the wild tomato species showed high moisture contents. The wild tomato cultivar had a higher crude protein content and quantitatively, represents the better source of protein intake when compared with the cultivated cultivars. The crude fibre content was highest in L. esculentum cv. Roma V.F. The ash content was higher in the lbadan local and wild cultivars than in the other cultivars. Peroxidase activity was found to be highest in L. pimpinellifoliun while catalase activity was highest in L, esculentum cv Ife-1. Glutathione transferase activities was negligible in all the samples analysed.